Clinical Presentation of Pleural Effusion Among Patients after CABG and its Prevalence - Iqtidar-Ud-Din, Muhammad Abdur Rauf, Yasir Arafat, Imran Khan, Bilal Mustafa, Tanveer Ahmad, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Pleural effusion often occurs after CABG. Usually, this effusion is slight and asymptomatic. There is also high symptomatic effusion, but in a small percentage of patients. Pleural effusion after CABG may be associated with significant morbidity and prolonged hospital stay. Early diagnosis and treatment can reduce morbidity of patients and extent of hospital stay. Aim: The aim of the study is to determine the risk factors and the severity of pleural effusion in patients after CABG. Place and Duration: In the Cardiology department of Qazi Hussain Ahmed Medical Complex, Nowshera for six-months duration from July 2020 to December 2020. Material and methods: The study was held among 120 patients after meeting the inclusion criteria and selected for the study. Patients were included in study population before referral for CABG from QHAMC to multicenters of Khyber Pakhtunkhwa. Their records were closely followed during admissions for CABG and post CABG and also assessed on various follow up visits. The study procedure was described to the patient and informed consent was obtained. Demographics, name, age, gender, surgery details, comorbidities such as COPD, EF and smoking were recorded on the attached form. The patients stayed in the intensive cardiac surgery unit for at least 7 days. The presence and severity of pleural effusion was assessed on the CXR. A chest x-ray was done on daily basis and evaluated by a chest specialist in the morning round. The amount of effusion in CXR was classified as follows: low effusion covering less than half of the chest, high effusion covering more than half of the chest. Possible risk factors for the development of pleural effusion in post-CABG patients have been reported. Results: The majority 99(82.5%) of the 120 subjects who had pleural effusion done with CABG were male. The patients mean age was 55.28 ± 10.47 years. Most patients 93(77.5%) had left pleurotomy. LIMA harvesting was reported in 98(81.7%) of patients. Most patients 100(83.3%) had left sided pleural effusions and 5(4.2%) had right sided and bilateral pleural effusions in 15(12.5%) of cases. A total of 102 patients (85%) had low (less than half of the chest) pleural effusion and large symptomatic pleural effusion in 18(18%) (more than half of the chest). 104 patients (86.7%) required pleural aspiration. Most of the patients 110(91.7%) had decreased serum albumin. Of the patients requiring effusion aspiration, 46 (38.3%) had dyspnea, 18 (15.0%) cough, 34 (28.3%) ABGs abnormalities, and 8 (7.7%) had atelectasis. Preoperative EF was normal in 80 (66.7%) patients, but poor EF was present in 50 (33.3%) patients on the 7th postoperative day. Conclusion: A slight left-sided effusion developed in the majority of patients after CABG. There was also large size of pleural effusion, but occurs in small extent. The effusion mainly causes some respiratory symptoms that require pleural aspiration. LIMA harvesting, pleurotomy and hypoalbuminemia were the main risk factors for pleural effusion in patients after CABG. Keywords: CABG = coronary artery bypass grafting, LIMA = Left internal mammary artery, CXR = chest X-ray, ICU = intensive care unit, COPD = chronic obstructive pulmonary disease and EF = ejection fraction.